Monetary policy regimes and inflation persistence in the United Kingdom - Shayan Zakipour-Saber (Queen Mary University of London, School of Economics and Finance, 2019)
This paper conducts a structural analysis of inflation persistence in the United Kingdom between 1965-2009. I allow for the possibility of shifts in the U.K. economy by estimating open-economy dynamic stochastic general equilibrium models in which parameters of a Taylor-type monetary policy rule, New Keynesian Phillips curve, and volatilities of structural economic shocks, follow Markov processes (Markov-switching DSGEs). The best-fitting model allows for changes in monetary policy and stochastic shock volatility. The first policy regime responds passively to movements in inflation, adjusting the nominal interest rate less than one-for-one and is estimated to be in place from the early 1970s until the late 1980s. The other regime responds actively to inflation and places less weight on exchange rate movements. This regime is present for the rest sample and almost coincides with the period after the Bank of England explicitly adopted an inflation target in 1992. I find a small but insignificant decrease in inflation persistence in the policy regime that responds more actively to inflation.
Keywords: C11; E31; E52; 330; Markov-Switching; DSGE; Inflation persistence; Bayesian estimation